Assessment of selected salt hydrates for thermochemical energy storage applications. (2022) - Padamurthy, Ankammarao; Nandanavanam, Jalaiah; Rajagopalan, Parameshwaran
Abstract: Inorganic salt hydrates are gaining popularity across the heat storage applications due to their good dehydration and hydration characteristics. The present study investigates the dehydration and hydration behaviour of the selected salt hydrates (SrBr2 ·6H2 O, LaCl3 ·7H2 O, MgCl2 ·6H2 O, and MgSO4 ·7H2 O) sequentially for four times using a differential thermogravimetric (DTG-60H) analyzer. The samples were initially heated from room temperature to 600 °C at different heating rates (2, 5, 10 and 20 °C/min) to understand the materials' behaviour. The dehydration temperatures and the associated enthalpies were observed to increase with the heating rates. For the tested heating rates, the dehydration temperatures and the enthalpies were found to have a range of 142–329 °C and 1420–3050 J/g respectively. The DTG curves suggest that the tested salts lose their water content mostly in the initial phase of heating. The mass loss due to dehydration up to 120 °C when heated at 5 °C/min ranges from 22% to 37%, which can be considered as a good sign for better enthalpies. The changes in mass due to the dehydration and hydration were almost same across the cycles tested, which confirms the materials' thermal stability. Among the tested salts, LaCl3 ·7H2 O exhibited better hydration enthalpies owing to its higher water vapour absorption capacity, ranging from 107.5 to 215.3 J/g. The present results indicate the materials' suitability for thermochemical energy storage applications if used with an appropriate temperature program.